Supported teaching autonomy support. [Enseñanza apoyada en el soporte de autonomía]. - Juan Antonio Moreno-Murcia (Ramón Cantó Alcaraz, 2016)
The findings obtained from the study and research into the consequences of applying determined teaching styles has led to a growing interest in this area among the scientific community. The student-centered and constructivist learning environments which enable students to gain a significant understanding through their own efforts has grown in importance compared with the traditional learning environment based on the transfer of learning by teachers (Oguz, 2013). In the context of the constructivist approach, students create their own knowledge by actively participating in the learning process (Wang, 2011), and by giving importance to the learners' autonomy. In these environments of interaction, the teacher becomes the learning facilitator, planning tasks and supporting responsibility for learning (Koç, 2006), providing students with options, helping them make their own decisions and solve problems for themselves. Consequently, this new focus provides students with opportunities to ask their own questions, and create their own learning concepts and strategies based on existing knowledge. The teacher has to accept students' autonomy and their enterprising spirit, and support them in this sense. In the context of this constructivist focus, one of the the main objectives of education is to promote students' autonomy (Öztürk, 2011).